Nanoparticle containing recombinant excretory/secretory-24 protein of Haemonchus contortus enhanced the cellular immune responses in mice - Hasan, Muhammad Waqqas; Haseeb, Muhammad; Gadahi, Javaid Ali; Ehsan, Muhammad; Wang, Qiangqiang; Lakho, Shakeel Ahmed; Haider, Ali; Aleem, Muhammad Tahir; Aimulajiang, Kalibixiati; Lu, Mingmin; Xu, Lixin; Song, Xiaokai; et al. (Frontiers in Veterinary Science, 2024)
Haemonchus contortus poses a global challenge as a parasite affecting small ruminants, yet the problem of absence of an effective vaccine against H. contortus infection still exists. This investigation sought to appraise the immunological reaction induced by recombinant H. contortus excretory/secretory-24 (rHcES-24) in combination with complete Freund’s adjuvant (CFA) and bio-polymeric nanoparticles (NPs) within a murine model. In this study, rHcES-24 was encapsulated in poly(d, l-lactide-co-glycolide) (PLGA) and chitosan (CS) NPs, administered subcutaneously to mice. Researchers analyzed the NPs using scanning electron microscope (SEM) and assessed lymphocyte proliferation, specific antibodies, cytokines, T cell proliferation (CD3e+CD4+, CD3e+CD8a+), and phenotypic alteration in splenocytes (CD11c+CD83+, CD11c+CD86+) through flow cytometry to understand the immune response. The results demonstrated that the administration of nanovaccines (NVs) prompted immune responses towards Th1 pathway. This was indicated by notable enhancements in the production of specific antibodies, heightened cytokine levels, and a robust proliferation of lymphocytes observed in mice that received the NVs compared to control groups. Remarkably, mice vaccinated with the antigen-loaded NPs formulations exhibited considerably higher proportions of splenic dendritic cells (DCs) and T cells in comparison to those receiving the traditional adjuvant or the control groups. Incorporating HcES-24 protein into NPs effectively conferred immunity against H. contortus, paving the way for developing a targeted and commercial vaccine.